A Cultural Legal Study of Speech Legality in Australian Film from the 1970s to 2010 ... - Weinert, Kim D (Griffith University, 2022)
This thesis is about the representation of Australian speech in film. Connecting with law and legality, this thesis reveals that speech and speech acts are a pivotal aspect of the cultural process and practice of Othering in Australia – a process that legislate an imagined Australian who is white and male, aggressively egalitarian and the beneficiary of settler state violence. Through a cultural legal analysis of four Australian films from the 1970s to 2010, this thesis focuses on speech, speech acts and silence to examine the practice of Othering of First Nations people (Where the Green Ants Dream, 1984), women (Don’s Party, 1976), immigrants (Romper Stomper, 1992) and the stereotypical, heterosexual white Australian male (Animal Kingdom, 2010). In doing so, this thesis offers a new way to explain and critique speech legality in Australia. The speech, speech acts and silences projected in these films highlight deep cultural and social divisions. Australians see and hear themselves through speech and speech ...